Salicylic Acid Regulates Indole-3-Carbinol Biosynthesis Under Blue Light in Broccoli Sprouts (Brassica oleracea L.) - Wang, Tao; Zhang, Derui; Yang, Boming; Su, Nana; Cui, Jin (Frontiers in Plant Science, 2022)
Indole-3-carbinol (I3C), an important secondary metabolite with strong anti-cancer ability, is widely found in cruciferous plants. Light and phytohormones are one of the most important external and internal signals, respectively that control the growth, development, and secondary metabolism of the plant life cycle. However, there are few studies about the influence of the blue light and salicylic acid (SA) on the regulation of I3C accumulation. In this study, a negative correlation was found between the content of I3C and SA in different species. Among this, broccoli and Arabidopsis thaliana were chosen for further studies. We observed that blue light treatment increased the accumulation of I3C, and exogenous SA treatment significantly inhibited the accumulation of I3C in broccoli sprouts. Based on the RNA sequence, the Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis indicated that blue light promoted the enrichment of differentially expressed genes (DEGs) in plant hormone signal transduction pathways. More specifically, down-regulated expression of genes related to SA biosynthesis and up-regulated expression of I3C genes related to metabolic pathway were observed under blue light. Taken together, these results suggested that SA negatively regulates blue light-induced I3C accumulation in broccoli sprouts.